Cross-Cultural Adaptation and Validation of the Co-Partner Indonesian Version - Eni Rahmawati; Yeni Rustina; Dessie Wanda; Nicole van Veenendaal; Kasiyah Kasiyah; M Agung Akbar (Jurnal Keperawatan Soedirman, 2026)
The CO-PARTNER instrument was developed to measure parental participation in neonatal care settings, but an Indonesian-language version is not currently available. The purpose of this study was to adapt the CO-PARTNER instrument for cross-cultural use in Indonesian. Cross-cultural adaptation was conducted following Sousa's guidelines. Psychometric testing was conducted between September and December 2025. Eligibility criteria for participants were parents of infants admitted to a neonatal care unit. The study involved 257 respondents. The questionnaire's structural variables were tested using Confirmatory Factor Analysis (CFA) in RStudio version 4.5.2. Based on established CFA criteria, one item (CCI 31) was eliminated due to low factor loading, resulting in a refined CO-PARTNER structure comprising 30 items across six domains. Cronbach’s alpha coefficients demonstrated strong internal consistency at both initial testing and retest for each of the six subscales (all > 0.70). Model fit indices showed satisfactory values: Comparative Fit Index (CFI) = 0.994; Root Mean Square Error of Approximation (RMSEA)=0.044; and degrees of freedom (DF)=390. The CO-PARTNER Indonesia Version proved to be a reliable and valid tool for evaluating parental involvement in infant care within neonatal care units across six key components: daily care, medical care, acquiring information, parent advocacy, time spent with the infant, and closeness and comforting of the infant. The CO-PARTNER Indonesia Version is applicable for assessing parental involvement in neonatal wards, where such participation contributes to improved outcomes for both infants and parents